Creating Product Value for Contemporary Digital Consumers with the Use of Modern Concept Sensory Marketing and Social Media - Anna KONDAK (Communications of International Proceedings, 2021)
The main aim of the study is to discuss sensory marketing practices and marketing activities implemented through social media in creating value for stakeholders, especially product value. Beginning with the theoretical aspects of the discussed issue, its essence was presented, an attempt was made to define the basic concepts and the tools, methods and procedures used were distinguished. Attention was focused on the role and possibilities of using various social media, including Facebook, Instagram, TikTok, YouTube, Snapchat. Bearing in mind the importance of methodical activities of marketers engaging stakeholders in communication on social networks, important issues related to the phenomenon of building online communities and co-creating value with the client were also raised. For the purposes of the study, literature studies were conducted, available research reports were reviewed and qualitative own research was carried out. The obtained results were used to formulate recommendations for marketers and business practitioners interested in the methodical use of the acquired assumptions when designing the message in the process of marketing communication and other activities creating value for stakeholders.
Keywords: Product Value; Sensory Marketing; Social Network Marketing